A CO funnel in the Galactic centre: molecular counterpart of the northern Galactic chimney - Veena, V. S.; Riquelme, D.; Kim, W.-J.; Menten, K. M.; Schilke, P.; Sormani, Mattia C.; Banda-Barragán, W. E.; Wyrowski, F.; Fuller, G. A.; Cheema, A. (Astronomy and astrophysics, 2023)
We report the discovery of a velocity coherent, funnel-shaped 13CO emission feature in the Galactic centre (GC) using data from the SEDIGISM survey. The molecular cloud appears as a low-velocity structure (VLSR = [ − 3.5,   + 3.5] km s−1) with an angular extent of 0.95° ×1°, extending towards positive Galactic latitudes. The structure is offset from Sgr A* towards negative Galactic longitudes; it spatially and morphologically correlates well with the northern lobe of the 430 pc radio bubble, believed to be the radio counterpart of the multiwavelength GC chimney. Spectral line observations in the frequency range of 85–116 GHz have been carried out using the IRAM 30-m telescope towards 12 positions along the funnel-shaped emission. We examine the 12C/13C isotopic ratios using various molecules and their isotopologues. The mean 12C/13C isotope ratio (30.6 ± 2.9) is consistent with the structure located within inner 3 kpc of the Galaxy and possibly in the GC. The velocity of the molecular funnel is consistent with previous radio recombination line measurements of the northern lobe of radio bubble. Our multiwavelength analysis suggests that the funnel-shaped structure extending over 100 pc above the Galactic plane is the molecular counterpart of the northern GC chimney.
Veröffentlicht: 27. Juni 2023
Gesehen am 23.08.2023